Granice lojalności w samorządzie terytorialnym - Stawecki, Marek (Annales. Etyka w Życiu Gospodarczym, 2010)
Local government is not free from dilemmas arising from ethical but illegal actions as well as legal, however, unethical ones. This breeds situations in which officials must decide whether to be loyal to the government authorities or citizens, whom they are obliged to serve. For instance, they must decide whether to accept the policy imposed by the district council making them change their clerical rules of conduct which, in their opinion, will be less favourably inclined to citizens. Consequently, they will be obliged either to take or refrain from taking certain actions, which stems from the inner imperative. At the root of this dilemma frequently lies a discord between law and ethics. The choice to be made leads to a moral dilemma. What is associated with this matter indeed is the question of revealing the truth about unethical, illegal, immoral or unlawful behaviour in the government that occurs with the employer’s silent approval. The so-called whistleblowing is the means to achieve it. The process is based on informing people or organizations who have the power to influence actions of the criticized individuals or organizations. This creates situations in which officials can no longer take advantage of two values and are made to choose only one of them.